Effect of Xiaoyaosan on Colon Morphology and Intestinal Permeability in Rats With Chronic Unpredictable Mild Stress - Ding, Fengmin; Wu, Jiajia; Liu, Chenyue; Bian, Qinglai; Qiu, Wenqi; Ma, Qingyu; Li, Xiaojuan; Long, Man; Zou, Xiaojuan; Chen, Jiaxu (Frontiers in Pharmacology, 2020)
Purpose: In our present study, a rat depression model induced by 6 weeks of chronic unpredictable mild stress (CUMS) was established, and we investigated how Xiaoyaosan affects the intestinal permeability of depressed rats and alterations of tight-junction proteins (TJ) involved in this process. Methods: The rat depression model was established using CUMS for 6 consecutive weeks. A total of 40 healthy male Sprague-Dawley rats were randomly sorted into 4 groups: the control group, CUMS group, Xiaoyaosan group and fluoxetine group. All groups, excluding the control group, were subjected to the 6-week CUMS program to generate the depression model. Body weight, food intake, and behaviors were observed during the modeling period. Histopathological alterations of colon tissue were evaluated by hematoxylin-eosin staining (H&E), and mucus-containing goblet cells were detected by periodic acid-Schiff (PAS) staining. The ultrastructural morphology of colonic mucosa was observed by transmission electron microscopy. Furthermore, immunohistochemistry (IHC) and quantitative reverse transcription polymerase chain reaction (qRT-PCR) were used to determine the expression of TJ. The concentrations of 5-hydroxytryptamine (5-HT) in the hypothalamus and colon were also assessed using enzyme-linked immunosorbent assay (ELISA). Results: Treatment of depressed rats with Xiaoyaosan alleviated depression-like behaviors, represented by an increase in total distance traveled, the number of entries into the central area of the open field test, the duration spent in the central area and sucrose preference. Xiaoyaosan treatment also increased body weight gain and food intake in depressed rats. Moreover, Xiaoyaosan treatment effectively improved the colonic pathological and ultrastructural changes, upregulated the expression of ZO-1, occludin and claudin-1 in the colon, and increased 5-HT levels in the hypothalamus and colonic mucosa. Conclusions: Xiaoyaosan treatment attenuates the depression-like behaviors caused by CUMS and ameliorates CUMS-induced abnormal intestinal permeability, which may be associated with the expression of TJ. These results suggest that Xiaoyaosan exerts an antidepressant effect that may be related to an improvement of intestinal barrier function via the brain-gut axis.